A Review on Helicobacter Pylori and Its Impact on Gut Health and Carcinoma: Review Article (Journal of Pharma Insights and Research, 2025)
Helicobacter pylori, a spiral-shaped, Gram-negative bacterium, colonizes the human gastric mucosa, affecting nearly half the global population. While many infections are asymptomatic, persistent colonization is a primary etiological factor for significant gastroduodenal diseases. This persistence is mediated by a sophisticated arsenal of virulence factors, including urease for acid neutralization, flagella for motility, and adhesins for epithelial attachment. Pathogenic strains, particularly those expressing the cytotoxin-associated gene A (CagA) and the vacuolating cytotoxin A (VacA), induce chronic inflammation, epithelial damage, and host immune modulation. The clinical spectrum of H. pylori infection ranges from chronic gastritis to peptic ulcer disease (PUD). H. pylori is classified as a Class I carcinogen and is the strongest identified risk factor for gastric adenocarcinoma, acting as the primary initiator of the Correa cascade. It is also causally linked to gastric mucosa-associated lymphoid tissue (MALT) lymphoma. Diagnosis relies on both invasive (endoscopy with biopsy, rapid urease testing, histology, culture) and non-invasive (urea breath test, stool antigen test) methods. Treatment is centered on antibiotic-based eradication regimens, typically involving a proton pump inhibitor and multiple antibiotics. However, the efficacy of these therapies is increasingly compromised by the rise in antimicrobial resistance, necessitating new treatments for management and prevention